Encyclopedia of Life Sciences 2016
DOI: 10.1002/9780470015902.a0026328
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Organismic Effects of Light Pollution

Abstract: Since the invention of the electric light bulb in 1879, a significant portion of the planet has been transformed from experiencing a natural pattern of light and dark determined by the sun, moon, stars and occasional other transient lights to being subjected to intermittent and perpetual illumination from human civilisation that is unprecedented in the history of Earth. The pervasiveness of this phenomenon and its exponential growth has measurable and significant consequences for living organisms. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…These night-time lights data have previously been used to track human population at many different scales (Zhang and Seto 2013). We acknowledge that although we use VIIRS night-time lights as a proxy for urbanization, species are differentially impacted by ambient light pollution (e.g., Longcore and Rich 2016), and it may be difficult to distinguish between whether species are responding to urbanization or night-time lights itself (i.e., ambient light pollution). Species respond differently to the intensity, direction, and duration of ambient light (Longcore and Rich 2016); most of which is not captured in the measurement of VIIRS night-time lights.…”
Section: Species-specific Urban Scoresmentioning
confidence: 99%
“…These night-time lights data have previously been used to track human population at many different scales (Zhang and Seto 2013). We acknowledge that although we use VIIRS night-time lights as a proxy for urbanization, species are differentially impacted by ambient light pollution (e.g., Longcore and Rich 2016), and it may be difficult to distinguish between whether species are responding to urbanization or night-time lights itself (i.e., ambient light pollution). Species respond differently to the intensity, direction, and duration of ambient light (Longcore and Rich 2016); most of which is not captured in the measurement of VIIRS night-time lights.…”
Section: Species-specific Urban Scoresmentioning
confidence: 99%
“…Unnatural lighting likely affects many biological functions as well as leading to numerous ecological consequences [ 10 , 12 , 13 , 69 , 70 , 71 , 72 ]. I focus on five biological functions: (1) Phenology and Circadian Rhythms; (2) Attraction and Orientation; (3) Foraging; (4) Predation; and (5) Reproduction.…”
Section: Unnatural Lighting Implications For Butterfliesmentioning
confidence: 99%
“…The emphasis in this arms race literature has been on the effects of temperature altering this developmental race; however, recent research has shown that anthropogenic lighting is altering the phenology of plants and trees as well [ 115 ]. Trees in unnaturally brighter areas budded seven days sooner than plants in areas without anthropogenic lighting [ 115 ] and this is likely across many different species of plants [ 10 , 13 , 70 ]. Thus, anthropogenic lighting is likely affecting the timing of both plant development and larvae development in unequal ways, which could lead to major disruptions in the coevolution between host plants and their insect larvae.…”
Section: Unnatural Lighting Implications For Butterfliesmentioning
confidence: 99%
See 2 more Smart Citations